PDTM-24. PINEOBLASTOMA SEGREGATES INTO MOLECULAR SUBTYPES WITH DISTINCT CLINICOPATHOLOGIC FEATURES: REPORT FROM THE RARE BRAIN TUMOUR CONSORTIUM. (11th November 2019) - Li, Bryan; Vasiljevic, Alexandre; Dufour, Christelle; Ho, Ben; Hwang, Eugene; Gururangan, Sridharan; Hansford, Jordan; Laquerriere, Annie; Delisle, Marie-Bernadette; Fangusaro, Jason; Forest, Fabien; Sumihito, Nobusawa; et al.
Abstract: BACKGROUND: Pineoblastoma (PB) is a rare but aggressive pediatric brain tumour arising from the pineal gland. Overall survival rates are estimated at 50–70%, with younger patients (< 5 years old) faring much worse (15–40%) despite intensive treatment regimens. Although germline RB1 and DICER1 alterations have been reported in a small proportion of PB, the clinical significance of such alterations and the biology of sporadic cases remains unknown. METHODS: We collected tumor tissue from 93 PB cases diagnosed at their referring centres. We undertook global DNA methylation profiling and performed multiple orthogonal consensus clustering analyses to elucidate PB subgroups. Chromosomal copy number alterations were determined using Conumee and GISTIC2, and whole exome or targeted sequencing was completed. Clinical data was analyzed with correlative statistical methods and outcomes were measured by Kaplan-Meier survival estimates. RESULTS: PB comprise five epigenetic groups, designated 1, 2, 3, 4A, and 4B. Deleterious, mutually exclusive alterations affecting miRNA biogenesis pathway members (DICER1, DROSHA, and DGCR8) were observed in 12/21 group 1 and 11/11 group 2 samples. Group 4A was characterized by recurrent RB1 loss and gain of the oncogenic miR-17/92, and group 4B by recurrent gain or amplification of MYC. These groups also exhibit distinct clinical features. PB groups 1–3 arose in older children (median ages 5.2–14.0 years) and had intermediate to excellent outcome (5-year OS of 71.9–100%). Group 4A and 4B were restricted to much younger children (median age 1.3–1.4 years) and had dismal prognoses (5-year OS 37.5% and 28.6%, respectively). CONCLUSIONS: PB divides into five groups with distinct genetic and clinical profiles. These findings will have important implications for precise patient stratification and form the foundation for preclinical studies of biology-informed therapies.